2015
DOI: 10.7860/jcdr/2015/14321.6674
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Dental Neglect Scale on Oral Health Status Among Different Professionals in Indore City-A Cross- Sectional Study

Abstract: The Dental Neglect Scale appears to be a sound method for objectifying dental neglect. It has many of the features of a satisfying health index. However, further validation with other age groups, cultures, place and a larger population is required in order to justify the utility of Dental Neglect Scale in different situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
1
16
0
5
Order By: Relevance
“…Skaret et al . [ 8 22 ] evaluated the reliability and construct validity of the Dental Neglect Scale given by Thomson et al . [ 10 ] and concluded that the scale may be a relevant instrument for population surveys which aim at identifying risk groups based on information about oral health, oral health-related behavior and attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skaret et al . [ 8 22 ] evaluated the reliability and construct validity of the Dental Neglect Scale given by Thomson et al . [ 10 ] and concluded that the scale may be a relevant instrument for population surveys which aim at identifying risk groups based on information about oral health, oral health-related behavior and attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…The term “Dental Neglect” can be defined as the behavior and attitudes which are likely to have detrimental consequences for the individual's oral health. [ 8 9 ] In other words, dental neglect is the failure to fulfill the known knowledge of oral health care for proper maintenance of oral cavity. [ 8 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Accomplished orthodontic treatment can improve multidimensional attitudes toward body image and mental health status [5]. Subsequently, an inappropriate aesthetic is the main reason for patients to undergo orthodontic treatment, while medical and dental indications are less prevalent as a reason for orthodontic treatment [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential that the person enduring orthodontic treatment are informed of these possible risks, so that they must be aware of their responsibilities during the treatment. [ 7 8 ] The present study found that 73% individuals enrolled for the study had high DNS that attributed to fair oral hygiene index among 45% and poor oral hygiene index among 15% of respondents. Maintenance of a healthy oral status demands a symbiotic relationship of the patient and dentist, which is the utmost important factor that determines the dental health and attitude of a person toward their dentition.…”
Section: Discussionmentioning
confidence: 56%